Isolated adrenal metastases of papillary thyroid carcinoma - Maciel, Joana (2022)
Funding Information: The authors thank the Pathology Department of Instituto Portugu?s de Oncologia de Lisboa Francisco Gentil for providing representative images of the histological slides.